2022
DOI: 10.3389/fpls.2022.878299
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization reduces root architecture plasticity in Ulmus pumila used for afforesting Mongolian semi-arid steppe

Abstract: In this study, we assessed the functional and architectural traits in the coarse roots of Ulmus pumila trees, which are used for afforesting the semi-arid steppe of Mongolia. Tree growth was supported by different watering regimes (no watering, 2, 4, and 8 L h−1) and by two types of soil fertilization (NPK and compost). In July, 2019, for each of these treatments six trees, outplanted in 2011 as 2-year-old seedlings from a container nursery, were randomly selected, excavated by hand, and digitized. The build-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 114 publications
2
22
0
Order By: Relevance
“…Under drier soil conditions, plants modulate the production of longer and finer roots, which results in a relatively greater length per unit mass, thereby leading to an increase in specific root length (SRL) (Ostonen et al, 2007;Montagnoli et al, 2012). Moreover, in terms of nutrient acquisition, root production has been related to lateral root branching since a reduced density is beneficial for N capture by reducing competition among root axes (Lynch, 2019;Montagnoli et al, 2022). Zadworny et al (2016Zadworny et al ( , 2017 proposed two ways of phenotypic plasticity that plants use to react to water or nutrient deficiency: quick growth of fine roots for a fast enhancement of water/nutrient acquisition, or thick root production to go in the direction of longterm ability to store resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under drier soil conditions, plants modulate the production of longer and finer roots, which results in a relatively greater length per unit mass, thereby leading to an increase in specific root length (SRL) (Ostonen et al, 2007;Montagnoli et al, 2012). Moreover, in terms of nutrient acquisition, root production has been related to lateral root branching since a reduced density is beneficial for N capture by reducing competition among root axes (Lynch, 2019;Montagnoli et al, 2022). Zadworny et al (2016Zadworny et al ( , 2017 proposed two ways of phenotypic plasticity that plants use to react to water or nutrient deficiency: quick growth of fine roots for a fast enhancement of water/nutrient acquisition, or thick root production to go in the direction of longterm ability to store resources.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their important role in the exploration and exploitation of water and nutrients, from a biomechanical point of view, preferential root production and growth occur in different directions to enhance anchorage along the axis of mechanical loading (Stokes et al, 2009). In slopy soils and/or under prevailing wind conditions, several authors have demonstrated that the tree anchorage is likely attributable to the forces of the roots pushing downward, hanging upward, or standing in the wind-or lee-ward direction (Danjon et al, 2005;Ghestem et al, 2011;Yang et al, 2014Yang et al, , 2017Montagnoli et al, 2022). These findings together explain that plants continuously adjust their root growth in response to environmental conditions through the modulation of new root production, longitudinal or radial growth, and the turnover of standing roots (Amendola et al, 2017;Montagnoli et al, 2021) and toward the achievement of higher functional performance.…”
Section: Introductionmentioning
confidence: 99%
“…The high salinity negatively affects the biochemical and physiological processes of plants (Giordano et al, 2021 ), such as the reduction of leaf surface, chlorophyll content, and the decrease in the photosynthetic efficiency of photosystem II (Kamran et al, 2020 ), and also inhibits plant growth by means of osmotic effects (Ma et al, 2020 ). Moreover, the root is the organ with the most direct exposure to adverse soil conditions, and its morphological plasticity is essential to withstand stress (Arif et al, 2019 ; Montagnoli et al, 2022 ). Salinity increases the proportions of fine roots improving the rhizosphere surface area so that plants can absorb more nutrients in low-nutrient soils (Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, forest trees also adjust their RSA to adapt to the changing external environment [12,13]. When roots encounter a nutrient-rich medium, trees increase [14] or decrease [15] lateral root growth near nutrient-rich areas. When nutrient-poor areas are present, the tree will suppress root growth in these areas.…”
Section: Introductionmentioning
confidence: 99%